Sex-For-Marks Scandals in South-East Nigeria Institutions of Higher Learning, Female Students Victim and the War against Sexual Harassment - O. Okafor, Samuel; O. Okoye, Elizabeth; C. Onu, Janefrances; C. Kekeocha-Christopher, Irene; E. Obiozor, Elizabeth; A. Okechukwu, Blessing; N. Ogbonna, Ann (Italian Sociological Review, 2022)
A number of studies have examined sexual harassment as it affects women and girls however; there are gaps in information in view of the magnitude of the incidence of sexual harassment in different parts of the world. The present study, inspired by the issue of sex-for-mark scandals in Nigerian institutions of higher learning, investigated the incidence of sexual harassment between female students and male staffs] across the institutions of higher learning in south east Nigeria. Guided by the Tripartite Model of sexual harassment and male dominance theory, the study adopted cross sectional survey involving 1200 female undergraduates (17+). Among the findings of the study, voluntary report of sexual harassment is correlated with perceived receptivity of the institution in handling sexual harassment of female students by male staff and female students (B=2.455, OR=11.644), secondary school gender (B=1.396, OR=4.041), source of sex education (B=.777, OR=2.176), availability of place to report sexual harassment in the institution (B=.509, OR=1.664), and religion of the students (B=.353, OR=1.423)p<.05. [...]